Direct Laser Writing to Generate Molds for Polymer Nanopillar Replication - Florea, Larisa; Delaney, Colm (My University, 2020)
Herein we exploit direct laser writing as a means to fabricate negative masters for the generation of polymeric nanopillars, via replica molding. Through optimization of design parameters, fabrication configuration, and polymerization protocols, we demonstrate for the first time, the fabrication of large-area negative templates which can be used to repeatedly produce some of the tallest (>1.5 μm) and thinnest (<300 nm) pillars ever achieved in biocompatible photocurable polymers, such as polyethylene glycol diacrylate, polypropylene glycol diacrylate, and polycaprolactone dimethacrylate. This combination serves to add value to two photon polymerization, and to extend its potential to the facile production of millimeter-sized arrays of submicron pillars, of infinite combination of height, diameter and pitch in a wide variety of compliant, biocompatible, and biodegradable materials.
PUBLISHED
Keywords: Biodegradable materials; Biocompatible photocurable polymers; Direct laser writing